Toleransi Antar Umat Beragama Perspektif Al-Qur’an (Jurnal Studi Al-Qur'an, 2023)
The Hudaibiyah agreement initiated by the Prophet Muhammad SAW initially marked tolerance in Islam. Tolerance in Islam is authentic, meaning it is not foreign and has even emerged since Islam existed. Because of its unique nature, tolerance in Islam is only a matter of implementation and commitment to practice it consistently. Nor is it for exchanging beliefs among the different religious groups. Tolerance here is in the sense of muammalah (social interaction). So there are common boundaries that may and may not be violated. This is the essence of tolerance, where each party must control themselves and provide space for mutual respect's uniqueness without feeling threatened by their beliefs or rights. Sharia has guaranteed that there is no compulsion in religion. Because forcing other people to follow our religion is a historical attitude which has no basis or example in the early history of Islam. It is precise with this fantastic tolerant attitude that the history of Islamic civilization has produced such brilliance that it is recorded in gold ink by the history of world civilization to this day and God willing in the future.